Disasters and Anthropology: An Interview with Rafael Mendoza - Potesta Cortez, Alexia (2021)
This interview aims to approach the topic of disasters from an anthropological perspective, with the viewpoint of a specialist on the topic, Dr. Rafael Mendoza (Ph.D in Anthropology, University of Florida). His approach to the concept of disaster views disaster as a process of rupture. Rupturing precisely what is deemed to be “normal” under certain social structures, therefore putting the very concept of “normal” into question, understanding it as a relative concept that is constantly being redefined by social actors, which has taken on a new meaning from the COVID-19 pandemic. It delves into the conceptual limits and implications of “disaster” and “normal” from an interdisciplinary approach which encompasses the anthropological discipline and qualitative studies. Likewise, the theoretical and methodological tools of the anthropology of disasters intersect with the COVID-19 pandemic. Therefore, there is a discussion about to what extent can a disaster be considered a disaster, considering the notions of a “new normal” of social actors. The interview was conducted virtually on Friday, January 22, 2020, in Lima and Quito simultaneously.